Removal of Failed Dental Implant with Application of Concentrated Growth Factor (CGF): A Case Report/ Nurul Ain Mohamed Yusof, Mohd Salman Masri and Erni Noor - Mohamed Yusof, Nurul Ain; Masri, Mohd Salman; Noor, Erni (2018)
High survival rates of dental implants were commonly reported even after 10 years of follow up. Nevertheless, complications and failure may occur and the implant would need to be removed. In recent years, the use of autogenous blood products in dental surgery has increased due to its ability to aid the healing of the soft and hard tissues. The case demonstrated the utilisation of concentrated growth factor (CGF) from the patient’s blood for healing following conservative removal of a failed dental implant. Subsequently, the patient showed satisfactory recovery without any infections and clinical complaints. This explantation procedure, together with the use of CGF, may prevent the normal bone resorption and accelerate soft tissue healing. As it is biological in nature having originated from the patient’s blood, it is more readily accepted by the tissues and the risk of infection is low.